INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM OLEH PEMBINA KEPADA HIMPUNAN ANAK PECINTA ISLAM (HAPIS) DI SMA NEGERI 3 TELUK KERAMAT - Rusli Rusli (CV. ADIBA AISHA AMIRA, 2022)
This study aims to reveal the process of internalizing the values ​​of Islamic religious education by coaches through extracurricular activities of Rohaniah Islam (ROHIS) and the factors that influence the internalization of Islamic education values ​​by coaches to the Association of Muslim Loving Children (HAPIS) at SMA Negeri 3 Teluk Keramat. The data source of this research is the information obtained from the supervisors and members of HAPIS. The method used in this research is descriptive method with a qualitative approach. Data collection techniques and tools are interviews, observation and documentation. The data that has been collected is then processed using data analysis, namely data reduction, data presentation or data display and drawing conclusions or verification. The results showed that 1) Internalization of Islamic education values ​​by the coach to the association of Muslim lovers (HAPIS) was carried out through association, role models, habituation, religious lectures, discussion and question and answer as well as introduction to nature or nature meditation. 2) Factors that influence the implementation of this internalization include internal factors or internal factors such as self-motivation, and external or external factors which include family, school and community environment.